Особенности разработки 3d модели корпуса промышленного компьютера для работы в агрессивной среде - Наливкин, А. Д. (ХНУРЕ, 2019)
The paper discusses the design features of industrial computer cases. Such computers functioning process in an aggressive environment are analyzed. The environment for 3D model implementation of hull is selected. Some recomendations for the design of industrial computers operating in aggressive environments are suggested.
Keywords: industrial computers; aggressive environment; 3D model; Solidworks